Kegiatan Donor Darah sebagai Salah Satu Cara Membantu Meningkatkan Kesehatan Diri dan Selamatkan Nyawa Sesama - Rina Veronica; Agustina; Elwindra; Fitria Prihatini; Evi Vestabilivy; Herlina; Ahmad Farid Umar; Mohammad Fatkhurrohman; Irma Nurmaisyah; Suratman (Health Care : Journal of Community Service, 2024)
Blood is a component needed by every living creature. Its role is very vital in distributing oxygen and other components needed by body cells. Blood donation is the process of taking blood from someone voluntarily to be stored in a blood bank to be used for blood transfusion purposes. Blood donors who regularly donate blood will get various benefits from blood donation. Apart from getting a free health check, at the start of the donation process, donors will also receive notification if there is a disease or virus in their blood. This will provide early detection for each donor and prevent the severity of the disease they are suffering from. The aim of this activity is to increase insight into the benefits of blood donation and save fellow humans who need blood. The methods used are counseling and blood donation activities. The partners in this activity were the community in Puri Gading Bekasi with 72 participants and the number of blood bags that met the requirements was 68 blood bags. The result of the activity was that the community was enthusiastic about the activity, which was also marked by the large number of questions received and blood bags that met the target.